High Vitamin D Levels May Downregulate Inflammation in Patients with Behçet's Disease - Fahd Adeeb; Maria Usman Khan; Xia Li; Austin G. Stack; Joseph Devlin; Alexander D. Fraser (Hindawi Limited, 2017)
Vitamin D plays a significant role in the immune system modulation and may confer a protective role in autoimmune diseases. We conducted a case-control study to compare 25(OH)D levels in patients with BD who were managed at a regional rheumatology programme in the midwest region of Ireland compared to matched controls. Healthy controls were selected from the Irish health system and matched in 1 : 5 ratio for age, sex, and the month of the year. 25(OH)D levels <20 nmol/L were classified as deficient while levels between 20 and 40 nmol/L were classified as insufficient. Differences between groups were assessed using Mann-Whitney test and associations between cases and controls were expressed as odds ratios and 95% confidence intervals. Nineteen patients with BD were compared with 95 controls matched by age, sex, and month of blood draw. 25(OH)D levels were significantly higher in patients in BD than in matched controls (median values: 45 nmol/L versus 22 nmol/L, p<0.005) and tended to be lower in patients with active disease than in those without (median values: 35 nmol/L (IQR: 22.75-47.25 nm/L) versus 50 nmol/L (IQR: 35-67 nmol/L), p=0.11). Compared to controls, patients with BD were significantly less likely to have 25(OH)D deficiency or insufficiency (OR: 0.09, 95% CI: 0.03-0.28, p<0.001). Our findings suggest a possible role for 25(OH)D in modifying the inflammatory response in BD and uncover a potential opportunity to assess whether correction of Vit D deficiency confers protective benefits.